The chain of custody is a necessary condition for the reduction of the risk of convicting innocents - Matida, Janaina (2020)
The subject of this paper is chain of custody of evidence. The introduction of this institute in Statute 13.964/19 reflects the recognition that reliability is an important characteristic of the pieces of evidence that will compose the set of evidence to be valued by the judge for the determination of the legally relevant facts. The function of the chain of custody of evidence, defined as the chronological documentation of the evidence (which must be understood broadly), is precisely to guarantee that the piece of evidence which the judge received in the phase of investigation is reliable, was collected, cataloged, manipulated, conditioned, and transported properly until it was brought to court; therefore, it can be used as a starting point for evidentiary inferences. In the absence of legislation, I argue that the appropriate phase for examining the chain of custody is the phase of admissibility; and, second, that the consequence of breaking the chain of custody should be the exclusion of the piece of evidence, avoiding its evaluation. The epistemic quality of the investigative phase is a necessary, albeit not sufficient, condition for a criminal trial seriously committed to the reduction of the risk of convicting innocents.